Using the Web Server Logs to Study Public Opinion - Gao, Yijun (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
With the help of webometrics techniques, we could explore whether or not the Web surfer’s online interest reflects the public opinion off-line. This paper investigates the Chinese Web user’s interest regarding the United States and Japan, and demonstrates that Web server log data could be a good source for us to gauge the public opinion on specific domestic and international issues. À l'aide de techniques webométriques, nous avons pu déterminer si les intérêts des internautes reflétaient l'opinion publique hors ligne. Cette communication porte sur les intérêts des internautes chinois pour les États-Unis et le Japon et démontre que les données des journaux de serveurs web peuvent être utiles pour prendre le pouls de l'opinion publique sur certains enjeux nationaux et internationaux.